The proper timing of virtual reality experience for reducing preoperative anxiety of pediatric patients: A randomized clinical trial - Ryu, Jung-Hee; Ko, Dayoung; Han, Ji-Won; Park, Jin-Woo; Shin, Aesun; Han, Sung-Hee; Kim, Hyun-Young (Frontiers in Pediatrics, 2022)
Background The virtual reality (VR) experience of an operation room (OR) prior to anesthesia and surgery has been known to reduce the anxiety and distress of pediatric patients. However, the proper timing needed for this is unknown. This randomized clinical study aimed to evaluate the proper timing of a VR tour of an OR (a few days before vs. immediately before anesthesia) to reduce the anxiety in a pediatric patient undergoing elective surgery. Methods The children from the ages of 4–10 years old were randomly divided into three groups. The control group received standard verbal information about the process of anesthesia and surgery 10 min before anesthesia. The VR A group experienced a VR tour at the outpatient clinic a few days before anesthesia, whereas the VR B group experienced the tour 10 min before anesthesia at the reception area of the OR. The 4-min VR video used in this study showed the experience of Pororo, an animation character, entering the OR and undergoing anesthesia. We evaluated the anxiety of children using the modified Yale preoperative anxiety scale (m-YPAS), the anxiety of caregivers using Beck anxiety inventory (BAI), and caregivers’ satisfaction. Results The m-YPAS of the VR B group was significantly lower than that of the control and VR A groups (p = 0.001), whereas there was no statistically significant difference in BAI (p = 0.605) among the 3 groups. The score of caregivers’ satisfaction with the overall process of anesthesia and surgery was higher in VR A group than in the control and VR B groups (p = 0.054). Conclusion The VR experience of an OR immediately before anesthesia was more effective than standard verbal information or a VR tour at the outpatient clinic a few days before anesthesia in reducing the anxiety and distress of children prior to surgery. Clinical trial registration [https://cris.nih.go.kr/cris/search/detailSearch.do/20773], identifier [KCT0006845].